Antecedents and consequences of nurses' burnout: Leadership effectiveness and emotional intelligence as moderators. Issue 4 (30th January 2018) - Chen, Shu-Chuan; Chen, Ching-Fu
Abstract : Purpose: Healthcare is recognized as a fertile field for service research, and due to the fact that nurses are stressed physically and emotionally, reducing burnout among frontline healthcare staff is an emerging and important research issue. The purpose of this paper is to explore the possible antecedents and consequences of nurses' burnout and to examine the moderating effects of personal trait and work-environment issue. Design/methodology/approach: Drawing on Bagozzi's (1992) reformulation of attitude theory (appraisal→emotional response→behavior), data from a survey of 807 nurses working in a major hospital in Taiwan were analyzed using the structural equation modeling technique and hierarchical regression analysis. Findings: The results reveal the positive causality between job stressors and nurses' burnout, whereas supervisor support negatively relates to burnout. In addition, the full moderating effects of leadership effectiveness and partly moderating effect of emotional intelligence on the relationships among job demands, job resources, and burnout are confirmed. Practical implications: The findings provide practical insight regarding how supervisors play an essential role in alleviating nurses' burnout. The supportive attitude and leadership effectiveness are recommended to be effectual managerial strategies. Originality/value: The empirical results support the job demands-resources model by applying reformulation of attitude theory. The work-environment issue surpasses the personal trait in moderating the relationships among job demands, job resources, and burnout.